Defining and modelling sesame stalk shear behaviour in harvesting by reciprocating cutting blade. (May 2023) - Soleimani, Narjes; Kamandar, Mohammad Reza; Khoshnam, Farhad; Soleimani, Amanollah
Abstract : The lack of synchronicity in the ripening of the sesame capsules causes an increase in seed loss at the time of harvest by existing machines. Little information is available concerning the effect of sesame stalk properties on the performance of impact cutting machines. To design a new and better sesame harvesting machine, real-time shear force and specific shear energy of sesame stalks in the impact cutting process were modelled and investigated. A series of laboratory and field tests were performed to model and measure the shearing properties of the stalk at the three moisture levels of 15, 30, and 60%, on a wet basis, at the four cutting speeds of 0.5, 1, 1.5, and 2 m s −1, and the three stalk positions of upper, middle, and lower region. The results of laboratory tests showed that at moisture content of 15%, the ratios of cutting force at the loading rate of 0.5–2 m s −1 are about 58%, 55%, and 40% and the ratios of specific shear energy are about 66%, 37%, and 39% at the upper, middle, and lower regions, respectively. Also, at the moisture content of 60%, the ratios of cutting force at the loading rate of 0.5–2 m s −1 are about 66%, 78%, and 83% and the ratios of specific shear energy are about 50%, 33%, and 30% at the upper, middle, and lower regions, respectively. Finally, to determine the maximum impact cutting force on the sesame field, the variation of impact shear force was modelled by an equation and the results of field tests showed that the maximum cutting force can be calculated by the equation and simple pendulum arm on the sesame field. When the characteristics of the physical characteristics of the sesame stalk are known, it is possible to calculate the maximum force for impact cutting of the stalks on the sesame field using a simple pendulum arm. Highlights: Possible to get maximum cutting force in sesame field with a simple pendulum arm. In 2nd and 3rd phases of stalk cutting, stalk resistance to penetration is zero. In 2nd and 3rd phases of stalk cutting, no resistance to blade movement. Cutting energy used to cut the outer layer of the stalk as blade leaves stalk.